Perception of old age among health professionals in the geriatric área - Mora Chavez , Tania Ninoska (2025)
This study aimed to analyse the effectiveness of different inclusive intervention models on the academic achievement of students with diverse educational needs in mainstream school settings. A systematic review of empirical and review studies published over the last decade was conducted, drawing on specialised education and social science databases. Explicit eligibility criteria were applied regarding the type of population, the school context, the description of the intervention model and the presence of learning outcomes, and a narrative synthesis was carried out that integrated quantitative and qualitative findings. The review identified models focused on inclusive policies, differentiated classroom practices, peer-mediated supports, pedagogical use of technologies and family participation, which showed positive associations with academic achievement when combined with continuous teacher professional development, cooperative classroom climates and adequate resources. At the same time, the evidence reviewed revealed experiences of limited inclusion, in which the lack of specialised support, rigid curricula and weak coordination with families reduced the impact of interventions on learning outcomes. Overall, the study concluded that inclusive education improved the academic achievement of students with diverse educational needs when it was conceived as a comprehensive process of transformation of policies, school cultures and pedagogical practices, and highlighted the need for more rigorous and context-sensitive research that deepened the understanding of the factors that conditioned such effectiveness.